IMPACT ON LIQUIDITY, SOLVENCY AND PROFITABILITY IN THE STOCK PRICE - Dewi Kusumowati; Ferdinandus Seran Deda (University of Merdeka Malang, 2022)
This study aims to examine and analyze the effect of liquidity ratios (current ratio, quick ratio), solvency (debt to equity ratio, debt to assets ratio), and profitability (return on assets, return on equity) on stock prices in the manufacturing sub-sector of automotive companies that listed on the Indonesia Stock Exchange. This research is quantitative descriptive. The population in this study is the automotive sub-sector companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The sample in this study was determined by purposive sampling method in order to obtain a sample of 10 companies and a total of 50 observational data. The data source used was secondary data obtained from the Indonesia Stock Exchange. The type of data in this study is quantitative data. The analysis technique used is the classical assumption test, multiple linear regression analysis, and hypothesis testing. The results showed that the Current Ratio, Debt to Equity Ratio, and Debt to Asset Ratio had no significant effect on stock prices. Meanwhile, Quick Ratio, Return on Assets, and Return on Equity have a significant effect on stock prices.